Translation between related languages in oral discourse: the case of some Italian discourse markers of reformulation - Solsona Martínez, Carmen (MonTi Monografías de Traducción e Interpretación, 2018)
The purpose of this contribution is to reflect on the translation of pragmatic markers in oral discourse and, in particular, on three Italian reformulation markers that present a rich variety of pragmatic values, as is the case of diciamo, insomma and cioè. We discuss the difficulty implied in the translation of these particles, the reasons of this difficulty, and the factors to be taken into account for translation (distribution, pragmatic functions, extralinguistic context, intonation) in order to attain an accurate translation, within the field of teaching Italian SL for Spanish speakers and translation of related languages. Within these markers, we will focus on the analysis of the translation of their non-prototypical values, that is, not so much on their metatextual values with a proper reformulation function, but on their metacommunicative and cognitive values, certainly more present in oral discourse.